Female runners’ satisfaction and motivation to participate: An examination of trail running event quality - Erdilanita, Ulma; Maharesti, Ayuning; Berliana (UIR Press, 2025)
Background: Event quality plays an important role in determining participant satisfaction and motivation to participate in the future. While there is a wealth of research on sport event quality and participant satisfaction, little has specifically explored the experiences of female runners in the context of trail running. This study fills this gap by highlighting women’s perspectives on trail running events. Research Objectives: This study aims to analyse the effect of trail running event quality on female runners' satisfaction and motivation, focusing on the BDG 100 Ultra event in Bandung. Methods: Using a cross-sectional study approach and purposive sampling technique, this study involved 24 female runners who had previously participated in trail running events. Data were collected through questionnaires measuring event quality, satisfaction, and motivation. Linear regression analysis was used to predict the relationship between event quality and female runner satisfaction and motivation. Findings and Results: The results of the analysis showed that event quality had a significant effect on female runner satisfaction (r = 0.870, p < 0.01), but its effect on motivation was relatively weak (r = 0.398, p > 0.05). This suggests that while event quality increases satisfaction, female runners’ motivation is more intrinsic. Most female runners participate because of the personal experience and pride in completing the challenge, not just the quality of the event. Conclusion: Event quality contributes to satisfaction, but female runners’ motivation is more influenced by personal experience and achievement. This study enhances the understanding of motivation in sport, particularly in female runners, and recommends inclusive and supportive event design to increase participation and satisfaction.